Components of primary care multimodal rehabilitation and their association with changes in sick leave: An observational study. - Severinsson, Yvonne; Grimby-Ekman, Anna; Nordeman, Lena; Holmgren, Kristina; Käll, Lina Bunketorp; Dottori, Maria; Larsson, Maria EH (Work, 2023)
BACKGROUND: To address the increase in sick leave for nonspecific chronic pain and mental illness, the Swedish government and the Swedish Association of Local Authorities and Regions entered into an agreement on a "Rehabilitation Guarantee" to carry out multimodal rehabilitation (MMR). OBJECTIVE: To investigate whether components of primary care MMR are associated with changes in sick leave. METHODS: A web-based survey was conducted in conjunction with a retrospective cross-sectional observational study of 53 MMR units. Sick leave data for the years before and after MMR completion was collected for 846 individuals. RESULTS: There was great disparity in how MMR was delivered. The average duration of rehabilitation was 4–8 weeks, and 74% of the MMR teams reported having fewer patients than recommended (≥20/year). Only 58% of the teams met the competence requirements. In-depth competence in pain relief and rehabilitation was reported by 45% of the teams and was significantly associated with fewer sick leave days after MMR (26.53, 95% CI: 3.65; 49.42), as were pain duration (17.83, 95% CI: –9.20; 44.87) and geographic proximity (23.75, 95% CI: –5.25; 52.75) of the health care professionals included in the MMR unit. CONCLUSIONS: In-depth competence and knowledge about the complex health care needs of patients seem essential to MMR teams' success in reducing sickness benefits for patients with nonspecific chronic pain and mental illness. Further research is needed to elucidate the optimal combination of primary care MMR components for increasing the return-to work rate and to determine whether involvement of the Social Insurance Agency or employers could support and further contribute to recuperation and help patients regain their previous work capacity.